Comment on Quintuple-ζ quality coupled-cluster correlation energies with triple-ζ basis sets by D. P. Tew, W. Klopper, C. Neiss and C. Hättig, Phys. Chem. Chem. Phys., 2007, 9, 1921 [erratum] - Tew, David P.; Klopper, Wim; Neiß, Christian; Haettig, Christof (Physical Chemistry Chemical Physics, 2008)
After rectifying a small programming error, CCSD(F12) correlation energies are even better than previously reported, particularly for double-ζ basis sets. © the Owner Societies.